THE QUALITATIVE STUDY OF LEADERSHIP AND EMPLOYEE PRODUCTIVITY (CASE STUDY: BRI UNIT TATAARAN) - Polii, Rionaldi E. (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT In this global era, any organization seeking to improve the quality of work of employees in order to generate productive employees. Bank Rakyat Indonesia (BRI) is one of the organizations in the banking sector which has the main tasks include managing and marketing the Micro Credit facilities. This study aims to determine the effect of leadership style on employee productivity. 13 employees of BRI Unit Tataaran were surveyed as respondents. This research using qualitative approach to examine and to explore deeply the experience of every individuals. The results shows the Leadership Style significant effect on employee productivity. While Employee Productivity is also influenced by the working environment. Instead, BRI Unit Tataaran should applying democratic leadership style, in order to create a new working environment with an atmosphere that is easier for employees and leaders to be more productive. While effective communication is needed to strengthen the leadership and employee relations. Keywords: Human Resource Management, Leadership, Employeeâ€™s productivity Â